THE ANALYSIS ON THE EFFECTS OF DEPOSIT INTEREST RATE, MONEY SUPPLY AND INFLATION ON HOUSEHOLD CONSUMPTION IN INDONESIA DURING 1983-2013 - Fachrudin, Feri; Wahyudi, Setyo Tri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The aim of this research is to acknowledge the macroeconomic variable’s influences of interest rate deposit, the amount of money supply (M2), and the inflation to the household’s consumption in Indonesia. The data used in this research is time series data from 1983 to 2013. After studying literature and testing the data using Error Correction Model (ECM) method, it showed that Interest Rate Deposit, money supply (M2) and inflation simultaneously have a significant effect in short term period and longed term period. Partially, Interest Rate Deposit has an unsignificant negative effect, The sum of money supply (M2) has a significant positive effect, and the inflation has a significant negative effect to the household’s consumption in short term period. While in longed term period, Interest Rate Deposit has a significant negative effect, the sum of money circulation (M2) and the inflation have a significant positive effect to the household’s consumption. Keywords: Household Consumption, Deposit Interest Rate, Money Supply (M2), Inflation, Error Correction Model (ECM).